2017
DOI: 10.1007/s11469-017-9829-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Probable Depression and Post-Traumatic Stress Disorder Among Female Sex Workers in Lilongwe, Malawi

Abstract: Globally, female sex workers (FSW) experience a high prevalence of mental health disorders, but in sub-Saharan Africa these are rarely identified. If left untreated, mental health disorders may place FSW and their partners at risk for HIV/sexually transmitted infections (STIs). We assessed the prevalence and correlates of probable depression, post-traumatic stress disorder (PTSD), and suicidal ideation (SI) in a cohort of 200 FSW in Lilongwe, Malawi. FSW completed the Patient Health Questionnaire-9 and the PTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 47 publications
(102 reference statements)
4
24
1
Order By: Relevance
“…The PHQ-9 was translated into the local language (Chichewa) and the same version was utilised in recently published studies examining postnatal depression in Malawi. 17,18 This version of the PHQ-9 was found to be in concordance with the Edinburgh Postnatal Depression Scale in our setting.…”
Section: Study Proceduressupporting
confidence: 63%
See 1 more Smart Citation
“…The PHQ-9 was translated into the local language (Chichewa) and the same version was utilised in recently published studies examining postnatal depression in Malawi. 17,18 This version of the PHQ-9 was found to be in concordance with the Edinburgh Postnatal Depression Scale in our setting.…”
Section: Study Proceduressupporting
confidence: 63%
“…Any woman with a PHQ‐9 score of ≥10, or who reported any suicidal ideation on the PHQ‐9, were referred for local mental health services. The PHQ‐9 was translated into the local language (Chichewa) and the same version was utilised in recently published studies examining postnatal depression in Malawi . This version of the PHQ‐9 was found to be in concordance with the Edinburgh Postnatal Depression Scale in our setting.…”
Section: Methodsmentioning
confidence: 89%
“…The pooled prevalence of anxiety among FSWs from LMICs is 21.0% (95% CI 4.8%-58.4%). PTSD symptomology was reported in 8 studies [9,10,23,40,43,46,47,50] with 4 studies included in the meta-analysis (Fig 4). The…”
Section: Plos Medicinementioning
confidence: 99%
“…Seventeen studies reported on suicidal ideation [10,36,39,46,47,55,57,58,61,69,71,[75][76][77][78][79][80]. Most assessed suicidal ideation by asking about suicidal thoughts, for example, "have you thought about killing yourself?"…”
Section: Plos Medicinementioning
confidence: 99%
See 1 more Smart Citation